Caracterização química de materiais pictóricos usados em escultura policromada : estudo de caso de uma escultura capixaba - Serrate, Júlia Wanguestel (2011)
Knowing the substances that constitute the works of art is indispensable to direct the intervention in the processes of restoration and conservation, also provides information about the historical time of the confection of the work, the understanding of the artist s technique and the recognition of forgeries. To the present work a polychrome sculpture was chosen. This sculpture consists in an image of Our Lady of Perpetual Help, from the parish with the same name in Itapemirim, witch would be restored at the Center of Conservation and Restoration of UFES (NCR-UFES). The techniques used to study the pigments and grounds witch constitute this work was the micro-chemical tests, polarized light microscopy (PLM) and infrared spectroscopy with transformed of Fourier (FTIR). To analyze the media it was used tests of solubility and FTIR. Some of the pigments and grounds could be identified by the three techniques, and the combination of micro-chemical tests and PLM presented the best sensibility, providing further results. The FTIR analyses enabled to detect only the substances witch were in great quantity. FTIR spectrum also provided information about the media that constitutes the repaints, but this analyses could not be done in the original painting, for this would require an amount of sample that would harm the work integrity. Test of solubility provided consistent results, but this kind of analyze is not easy to visualize, and can generate ambiguous results if it is not confronted with another technique